THE EFFECTIVENESS OF OUTLINING IN IMPROVING STUDENTS’ PARAGRAPH WRITING SKILL - Tenny Murtiningsih (UMBanjarmasin, 2019)
This is classroom action research. The objective of this research is to find out the effectiveness of outlining in improving students’ paragraph writing skill for English Department Students, Teacher Training and Education Faculty, University of Muhammadiyah Banjarmasin. There are 6 students as the respondent of this research. The researcher took them as the respondent when they studied Writing 2 subject. The researcher got the data from the treatment in 2 cycles that were conducted in this research, the questionnaire that was distributed to the respondents above and also the observation during the cycles. The descriptive analysis in cycle 1 shows that the mean score is 71.3333, the minimum score is 63.00, the maximum score is 80.00 and the standard deviation is 5.85377. Meanwhile cycle 2 shows that the mean score is 76.6667, the minimum score is 70.00, the maximum score is 85.00 and the standard deviation is 5.16398. The research result explains that there is significant improvement in students’ paragraph writingskill by using outlining. The student’s paragraph writing skill is improved. Beside that the result of questionare and observation shows that outlining really works to improve students’ paragraph writing skill.